HARMONY IN WASTE: EMPOWERING WOMEN FOR OPTIMAL WASTE MANAGEMENT AND WEALTH CREATION - Muhammad Nazaruddin Yuli (Journal of Management and Economics, 2024)
This research, titled "Harmony in Waste: Empowering Women for Optimal Waste Management and Wealth Creation," explores the intersection of women's empowerment and waste management initiatives. Employing a multidimensional approach, the study investigates the role of women in optimizing waste management practices and the subsequent creation of wealth from waste. Through a combination of surveys, interviews, and case studies, the research aims to unravel the social, economic, and environmental impacts of women-led waste management initiatives, contributing to sustainable development.